Analisis Sosial dan Ekonomi Usahatani Padi Sawah dan Usaha Industri Kecil Batu Bata di Kecamatan Landono Kabupaten Konawe Selatan - Sari, Heksni Rapindan; Sidu, Dasmin; Nalefo, La (Department of Agribusiness, Halu Oleo University, 2019)
This study aims to (1) find out the social conditions of wetland rice farmers in Landono II Village and brick entrepreneurs in Abenggi Village, Landono Subdistrict, South Konawe Regency (2) to find out the economic conditions of rice paddy farmers in Landono II Village and brick entrepreneurs in Abenggi Subdistrict Village Landono, Konawe Selatan District and (3) to find out the reason farmers switch business from rice farming to small brick industry businesses in Abenggi Village, Landono District, South Konawe Regency. The data analysis used is qualitative and quantitative analysis. The results showed that (1) the social conditions of wetland rice farmers in Landono II Village were active in group activities while the brick entrepreneurs in Abenggi Village were not active in group activities. (2) The economic condition of lowland rice farmers in Landono II village is sufficient for daily needs and for brick entrepreneurs in Abenggi Village better than when cultivating lowland rice (3) The reason rice farmers are shifting to small brick industry is dominated by income from small brick industry business is greater than income on wetland rice farming (83%).